2000
DOI: 10.1139/x00-076
|View full text |Cite
|
Sign up to set email alerts
|

Throughfall and fog deposition of nitrogen and sulfur at an N-limited and N-saturated site in the San Bernardino Mountains, southern California

Abstract: Inorganic nitrogen (N) and sulfur (S) deposition in bulk throughfall and fog were determined at two sites located at opposite ends (42 km apart) of a pollution gradient in the San Bernardino Mountains. Plot-level averages for total annual N and S deposition in throughfall in 1996 were 18.8 and 2.9 kg·ha-1, respectively, at Camp Paivika (CP) and 2.9 and 0.4 kg·ha-1, respectively, at Barton Flats (BF). Deposition of N in throughfall in the four transects at CP ranged from 12.1 to 31.7 kg·ha-1·year-1. Spatial var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…As a result of the Mediterranean climate, dry nitrogen deposition plays a dominant role during the long dry summers, in contrast to much of northern Europe and northeastern North America, where a larger fraction of nitrogen deposition occurs as acidic precipitation (5). Furthermore, deposition of nitrogen in fog is also substantial in the San Bernardino Mountains, particularly in the spring and fall (18). These forest soils are also unique in that nitrate concentrations at the most N-impacted site are considerably higher than in any other soil previously reported in the literature (16,17).…”
mentioning
confidence: 84%
“…As a result of the Mediterranean climate, dry nitrogen deposition plays a dominant role during the long dry summers, in contrast to much of northern Europe and northeastern North America, where a larger fraction of nitrogen deposition occurs as acidic precipitation (5). Furthermore, deposition of nitrogen in fog is also substantial in the San Bernardino Mountains, particularly in the spring and fall (18). These forest soils are also unique in that nitrate concentrations at the most N-impacted site are considerably higher than in any other soil previously reported in the literature (16,17).…”
mentioning
confidence: 84%
“…In 1990 pH values in a survey of the same region were generally within the range of pH 4.6 to 5.7 (WOOD et al 1992;WOOD 1994). Soil acidification due to atmospheric deposition in southern California is presumably from N deposition, because S deposition is low in this region (FENN et al 2000).…”
Section: Mixed Conifer and Chaparral In Southern Californiamentioning
confidence: 99%
“…The above comparisons indicate that large amounts of sulfate and nitrogen deposit on the deciduous forests at Lake Mashu by fog water deposition as well as wet deposition due to precipitation. Prior studies have found that the amount of inorganic ions deposited by fog water is a large proportion of the total (Klemm and Wrzesinsky, 2007;Igawa et al, 2002;Fenn et al, 2000;Kobayashi et al, 1999).…”
Section: Estimation Of Fog Water and Inorganic Ion Depositionmentioning
confidence: 99%
“…Such acid fog deposits on vegetative surfaces and is harmful to plants (Schaberg et al, 2000;Jacobson et al, 1989;Schemenauer, 1986). In addition, fog water deposition significantly contributes to hydrological, nutrient and pollutant inputs to forest ecosystems (Ewing et al, 2009;Fenn et al, 2000;Dawson, 1998), and it may affect the woodland along the somma of Lake Mashu. Nevertheless, the fog water deposition on the woodland in the area, which can cause supply considerable amounts of pollutants and nutrients, has still not been investigated.…”
Section: Introductionmentioning
confidence: 99%